Сутність, зміст і характерні ознаки системи забезпечення публічної безпеки в Україні - Аброськін, В. В.; Abroskin, V. V. (Науковий вісник публічного та приватного права. - 2017. - Вип. 6, т. 4. - С. 163-167, 2017)
У статті розглянуто сутність, зміст і характерні ознаки системи забезпечення публічної безпеки в Україні. Проаналізовано підходи до розуміння сутності категорії «система». Визначено, що система забезпечення публічної безпеки в Україні має структурований та динамічний характер. Основними змістовними елементами такої системи є її суб’єкти. Окрім цього, серед елементів системи забезпечення публічної безпеки в Україні названо її об’єкт та діяльність її суб’єктів. Надано авторське визначення сутності системи забезпечення публічної безпеки в Україні.

The purpose of the article is to identify the nature, characteristics and content of the system of public security in Ukraine. This goal is achieved through an analysis of approaches to understanding the essence of the category “system”. The conducted analysis shows that in most cases, any system is considered as a complex of elements functioning within it, which have stable relationships. It is revealed that the system of public security in Ukraine has the features that characterize it as a system. Among such signs it is named: structuring, which implies the presence in its composition of interrelated and interconnected elements; a dynamic character that shows that for its proper and efficient functioning it undergoes constant changes; the presence of stable ties between its elements, which are determined by the common goals and tasks of functioning and existence of this system – ensuring public safety in Ukraine. The content of the public security system in Ukraine is determined by implementing the characteristics of its structural elements. Its subjects are the main structural element of the public security system in Ukraine. Actually, ensuring public security in Ukraine is considered as its next element – the object of this system. It is emphasized that the connection between the subjects of the system of ensuring public safety and its object is manifested in the activities of such entities, which is realized through the appropriate forms and methods. Proved that under the system of ensuring public safety in Ukraine should be understood organically combined set of entities with activities that implemented them using appropriate forms and methods in order to ensure and maintain the proper state of public safety in Ukraine.

В статье рассмотрены сущность, содержание и характерные признаки системы обеспечения общественной безопасности в Украине. Проанализированы подходы к пониманию сущности категории «система». Определено, что система обеспечения общественной безопасности в Украине имеет структурированный и динамический характер. Основным содержательным элементом такой системы являются ее субъекты. Кроме этого, среди элементов системы обеспечения общественной безопасности в Украине названы ее объект и деятельность ее субъектов. Предоставлено авторское определение сущности системы обеспечения общественной безопасности в Украине.
Keywords: публічна безпека; забезпечення публічної безпеки; система забезпечення публічної безпеки; суб’єкти забезпечення публічної безпеки; public security; ensuring public safety; public security system; subjects of public safety; публичная безопасность; обеспечение общественной безопасности; система обеспечения общественной безопасности; субъекты обеспечения общественной безопасности